Pre-pulse inhibition and striatal dopamine in subjects at an ultra-high risk for psychosis. (June 2014) - De Koning, Mariken B; Bloemen, Oswald JN; Van Duin, Esther DA; Booij, Jan; Abel, Kathryn M; De Haan, Lieuwe; Linszen, Don H; Van Amelsvoort, Thérèse AMJ
Reduced prepulse inhibition (PPI) of the acoustic startle response is thought to represent a robust biomarker in schizophrenia. Reduced PPI has been demonstrated in subjects at ultra high risk (UHR) for developing psychosis. Imaging studies report disruption of striatal dopaminergic neurotransmission in patients with schizophrenia. First, we compared the PPI of the acoustic startle response in UHR subjects versus healthy controls, to see if we could replicate previous findings of reduced PPI; secondly, we investigated our hypothesis that PPI would be negatively correlated with striatal synaptic dopamine (DA) concentration. We measured the startle reactivity and PPI of the acoustic startle response in 14 UHR subjects, and 14 age- and gender-matched healthy controls. Imaging of 11 UHR subjects and 11 healthy controls was completed by an [ 123 I]-IBZM (radiotracer for dopamine D2/3 receptors) SPECT, at baseline and again after DA depletion with alpha-methyl-para-tyrosine (AMPT). The percentage change in striatal [ 123 I]-IBZM radiotracer binding potential is a proxy of striatal synaptic DA concentration. UHR subjects showed reduced PPI, compared to control subjects. In both UHR and control subjects, there were no significant correlations between striatal synaptic DA concentration and PPI. We provide further evidence for the hypothesis that these two biomarkers are measuring different aspects of pathophysiology.